Subliminal voices: barriers to healthcare and proposed interventions by international students and their families at a large research university in the Midwest - Sen, Soumitro (Frontiers in Communication, 2023)
Despite the vast numbers of international students in the U.S. as well as their contribution to the economy, their voices are rarely heard within the discursive spaces of the American academe. This study takes a step toward filling that gap and seeks to open up a platform where married, international graduate students at a large Midwestern university could communicate, in particular, the barriers they faced while accessing healthcare facilities for their families. Using a culture-centered approach to health communication, through focus groups and in-depth interviews, this study provides a discursive space where 22 international students and spouses articulate vivid narratives of the problems they encountered while negotiating the American healthcare system, revealing a basic issue of unaffordability of students' spousal health insurance, accompanied by a dire need for better communication between international students and the university, with there being a need for the latter to better explain to international students a healthcare system that is new to them, as well as communicating with them, with better clarity, the available healthcare options for them and their spouses. The participants also proposed interventions to redress the problems, including the need for better dissemination of information regarding healthcare.